Calcium Serum Levels and Blood Pressure Response in trained subjects who consumed goat milk - Yusni Yusni; Ieva Baniasih Akbar; M. Rizki Akbar (Jurnal Kardiologi Indonesia, 2017)
Background: Calcium plays a role in regulating blood pressure and one exogenous sources of calcium are goat milk. Indonesian society is generally believed that goat milk can lower blood pressure and useful as antihypertensive, but so far have not found scientific evidence of how the mechanism of goat milk for controlling blood pressure. This study aimed to analyze the effect of the consumption of goat milk for lowering blood pressure and its relation to calcium serum levels in people trained. Method: Subjects, 19 gymnasts (the treatment group) and 10 runners (the control group), male and female, aged 17-28 years. Treatment: goat’s milk 250 mg / day, administered after dinner (at 19:00 to 20:00 pm), for 90 days. Design research is quasy experimental pretest-posttest design. Analysis of data using normality test Kolmogorof Smirnof-Z (p>0.05), Levene homogeneity test (p>0.05), t test (p<0.05) and Pearson correlation test (p <0.05). Results: The results showed systolic blood pressure after consume goat milk decreased significantly in the treatment group compared to the control group (122 ± 7:33 and 10:54 ± 115 vs 119 ± 7.61 ± 4.83 mmHg and 118 mmHg; p <0.05), whereas diastolic blood pressure in the treatment group and the control group (80.42 ± 5:53 and 7:08 ± 78.42 mmHg vs; 78.50 ± 3:37 and 3:16 ± 79 mmHg; p> 0.05) did not show differences after administration of goat’s milk. Serum calcium levels after administration of dairy goats in the treatment group increased significantly compared with the control group (9:47 ± 0:25 and 0:32 ± 9.87 mg / dl vs 9.74 ± 0:42 and 9:37 ± 0:38 mg / dl; p <0.05). The results of Pearson correlation test (r) showed r=-0.45; p=0.05, meaning there were nonsignificant correlation between systolic blood pressure with serum calcium levels. Conclusion: Delivery of goat’s milk can decrease systolic blood pressure and stimulates the secretion of calcium, but a decrease in systolic blood pressure was not associated with increased serum calcium levels in people trained. Abstrak Latar Belakang: Kalsium berperan dalam mengatur tekanan darah dan salah satu sumber kalsium eksogen adalah susu kambing. Masyarakat Indonesia umumnya percaya bahwa susu kambing dapat menurunkan tekanan darah dan bermanfaat sebagai antihipertensi, namun sejauh ini belum ditemukan bukti ilmiah bagaimana kerja susu kambing dalam mengontrol tekanan darah. Penelitian ini bertujuan menganalisis pengaruh konsumsi susu kambing dalam menurunkan tekanan darah dan hubungannya dengan kadar kalsium serum pada orang terlatih. Metode: Subjek, 19 pesenam (kelompok perlakuan) dan 10 atlet lari (kelompok kontrol), laki-laki dan perempuan, usia 17-28 tahun. Perlakuan: pemberian susu kambing 250 mg/hari, diberikan setelah makan malam (pukul 19.00-20.00 wib), selama 90 hari. Design penelitian adalah quasy experimental pretest-posttest design. Analisis data menggunakan uji normalitas Kolmogorof Smirnof-Z (p>0,05), uji homogenitas Levene (p>0,05), uji t (p<0,05) dan uji korelasi pearson (p<0,05). Hasil: hasil penelitian menunjukkan tekanan darah sistolik setelah pemberian susu kambing pada kelompok perlakuan menurun signifikan dibandingkan kelompok kontrol (122±7.33 dan 115±10.54 vs 119±7.61 dan 118±4.83 mmHg mmHg; p<0,05), sedangkan tekanan darah diastolic pada kelompok perlakuan dan kelompok kontrol (80.42±5.53 dan 78.42±7.08 mmHg vs; 78.50±3.37 dan 79±3.16 mmHg; p>0,05) tidak menunjukkan perbedaan setelah pemberian susu kambing. Kadar kalsium serum setelah pemberian susu kambing pada kelompok perlakuan meningkat signifikan dibandingkan dengan kelompok kontrol (9.47±0.25 dan 9.87±0.32 mg/dl vs 9.74±0.42 dan 9.37±0.38 mg/dl; p<0,05). Hasil uji korelasi pearson (r) menunjukkan r=-0,45; p=0,05, artinya terdapat korelasi sedang yang tidak bermakna antara tekanan darah sistolik dengan kadar kalsium serum. Kesimpulan: Pemberian susu kambing dapat menurun tekanan darah sistolik dan merangsang sekresi kalsium namun penurunan tekanan darah sistolik tidak berhubungan dengan peningkatan kadar kalsium serum pada orang terlatih.